VD_FINDINFO ML / 2010 / 168 vom 4. März 2010 - VD Tribunal cantonal (2010)
MAINLEVÉE DÉFINITIVE, COTISATION AVS/AI/APG, DÉCISION DE COTISATIONS | 97 al. 1 LAVS, 80 LP, 52 LPGA, 54 al. 1 LPGA, 34a RAVS